Comparative studies on manganese-based SOD mimetics, including the phosphate effect, by using global spectral analysis - Friedel, Felix; Lieb, Dominik; Ivanovic-Burmazovic, Ivana (Journal of Inorganic Biochemistry, 2012)
Stopped-flow measurements have been successfully combined with time-resolved UV/vis spectroscopy and global spectral analysis of superoxide decay for the comparative study of catalytic activity of putative manganese SOD (superoxide dismutase) mimetics known in the literature. The SOD activity of the studied complexes decreases in the following order: a) M40403 > Mn(III)TM-4-PyP > Mn(II)pyane > > EUK-113 at pH 7.4 (M40403 = ([manganese(II)dichlorido(4R,9R,14R,19R)-3,10,13,20,26- pentaazatetracyclo[20.3.1.0.4,9014,19]hexacosa-1(26),-22(23),24-triene], Mn(III)TM-4-PyP = Mn(III)meso-tetrakis(N-methylpyridinium-4-yl) porphyrin, Mn(II)Pyane = Mn(II)trans-2,13-dimethyl-3,6,9,12,18- pentaazabicyclo[12.3.1]-octadeca-1(18),14,16-triene, EUK-113 = [manganese(III)acetato(6,6′-((1E,1′E)-(ethane-1,2- diylbis(azanylylidene))bis(methanylylidene))bis(2-methoxyphenolate)]) in Hepes buffer (Hepes = 4-(2-Hydroxyethyl)piperazine-1-ethanesulfonic acid), b) Mn(III)TM-4-PyP > M40403 ≅ Mn(II)pyane ≫ EUK-113 at pH 8.1 in Hepes buffer and c) Mn(III)TM-4-PyP ≅ Mn(II)pyane > MnCl > M40403 ≅ EUK-113 at pH 7.4 in phosphate buffer. MnCl in Hepes, Mn(III)TSPP , Mn(III)TBAP , Mn(III)acetate, Mn(II)lactate and Mn(II)EDTA do not exhibit SOD activity (Mn(III)TSPP = Mn(III)mesotetrakis(benzoic acid)porphyrin, Mn(III)TBAP = Mn(III)mesotetrakis(4-sulfonatophenyl)porphyrin). MnCl possess SOD activity that is comparable with those of other mimetics in the presence of phosphate. Our results demonstrate that phosphate anions, independent of ionic strength effect, influence the activity of manganese SOD mimetics, which is crucial for understanding and comparing their biological activity. © 2011 Elsevier Inc. All rights reserved.

Determination of the diffusion coefficient of CO 2 in the ionic liquid EMIM NTf 2 using online FTIR measurements - Kortenbruck, Kerstin; Pohrer, Benjamin; Schlücker, Eberhard; Friedel, Felix; Ivanovic-Burmazovic, Ivana (Journal of Chemical Thermodynamics, 2012)
Physical data concerning the absorption kinetics like the diffusion coefficients are important values for designing an economically working gas separation processes. Considering ionic liquids, which emerged in recent years as interesting alternative solvent media for versatile industrial purposes, usually only solubility data for gases are available if at all. Therefore in order to gain additional information such as diffusion coefficients of gases in ionic liquids, we established an efficient and easily assembled set-up based on time-resolved FTIR measurements. Applying this methodology, the diffusion coefficient of carbon dioxide in 1-ethyl-3-methyl-imidizolium bis[(trifluoromethyl)sulfonyl]amide (EMIM NTf ) was determined at a temperature of 303 K. © 2011 Elsevier Ltd. All rights reserved.

Dinuclear seven-coordinate Mn(II) complexes: Effect of manganese(II)- hydroxo species on water exchange and superoxide dismutase activity - Lieb, Dominik; Friedel, Felix; Yawer, Mirza; Zahl, Achim; Khusniyarov, Marat; Heinemann, Frank Wilhelm; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2013)
Two dinuclear seven-coordinate manganese(II) complexes containing two pentaazamacrocyclic subunits, with imine or amine functionalities, respectively, have been synthesized and characterized in the solid state as well as in aqueous solutions of different pH, by performing X-ray structure analyses, SQUID, potentiometric, electron spray ionization-mass spectrometry (ESI-MS), electrochemical, and (17)O NMR water exchange measurements (varying temperature and pressure), and by determination of SOD activity. The two manganese(II) centers within the dinuclear structures behave independently from each other and similarly to the manganese centers in the corresponding mononuclear complexes. However, the dinuclear amine complex possesses increased complex stability and acidity of the coordinated water molecules (pK(a2) = 8.92) in comparison to the corresponding mononuclear analogue. This allowed us to observe a stable trans-aqua-hydroxo-Mn(II) species in an aqueous solution and to study for the first time the trans-effect of the hydroxo group on the water lability on any divalent metal center in general. The observed trans-labilizing effect of the hydroxo ligand is much smaller than in the case of aqua-hydroxo-M(III) trivalent metal species. Whether this is a general property of trans-aqua-hydroxo-M(II) species, or if it is specific for Mn(II) and/or to the seven-coordinate structures, remains to be seen and motivates future studies. In addition, an influence of the hydroxo ligand on the SOD activity of manganese(II) complexes could be evaluated for the first time as well. Compared with the mononuclear analogue, which is not able to form stable hydroxo species, our pH dependent studies on the SOD activity of the dinuclear amine complex have indicated that the hydroxo ligand may promote protonation and release of the product H(2)O(2), especially in solutions of higher pH values, by increasing its pK(a) value.